1978
DOI: 10.1677/joe.0.0790215
|View full text |Cite
|
Sign up to set email alerts
|

Specific Interaction of Corticosteroids With Binding Sites in the Plasma Membranes of the Rat Anterior Pituitary Gland

Abstract: The binding of glucocorticoids to a crude fraction of rat pituitary plasma membranes and to solubilized membrane proteins was measured. The binding characteristics were similar to those exhibited by transcortin: radioactive corticosterone was bound to a greater extent than radioactive dexamethasone and labelled corticosterone, but not labelled dexamethasone, was displaced by unlabelled corticosterone, deoxycorticosterone and progesterone. A Scatchard plot of the binding data revealed the presence of a binding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
24
0

Year Published

1981
1981
2007
2007

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(29 citation statements)
references
References 12 publications
5
24
0
Order By: Relevance
“…In anterior pituitary cells, CBG is found in membrane fractions in addition to the cytosol compartment (Koch et al 1978). Membrane-bound and cytosolic CBG (transcortin) levels in the pituitary have both been shown to parallel the changes in circulating CBG concentrations (Koch et al 1978, Tannebaum et al 1997.…”
Section: Discussionmentioning
confidence: 99%
“…In anterior pituitary cells, CBG is found in membrane fractions in addition to the cytosol compartment (Koch et al 1978). Membrane-bound and cytosolic CBG (transcortin) levels in the pituitary have both been shown to parallel the changes in circulating CBG concentrations (Koch et al 1978, Tannebaum et al 1997.…”
Section: Discussionmentioning
confidence: 99%
“…Cell fractionation studies showed association of the CBG-like binding system at the plasma cell membrane [16] and the protein probably can be internalized via the membrane in tissues, such as the pituitary, which has a protein permeable vascular bed [18]. That membrane components may be involved in glucocorticoid uptake became evident in work with a pituitary tumor cell line .…”
Section: Discussionmentioning
confidence: 99%
“…Principal localization of the labelled dexamethasone-receptor complex was found in the corticotrophs, and to a lesser extent in gonadotrophs, somatotrophs and cells stained with antisera to prolactin [I I] The CBG-like binding system is present in pituitary cytosol after extensive perfusion [13] and remains associated with isolated pituitary celts [IS]. Besides cytosol also membrane preparations of the pituitary displayed binding specificity similar to that displayed by the CBG-like binding system [16]. Immunocytochemical observations reported from this laboratory [17] and from elsewhere [18] indicated intracellular localization of the CBG-like binding system in the pituitary.…”
Section: Introductionmentioning
confidence: 99%
“…The circulating level of CBG indeed plays a crucial role in the extent to which the unbound moiety of glucocorticoids is transferred into the liver and hence in the biological activity of these steroids [43]. Moreover, the localization of receptors for CBG on cell membranes [13], and especially on hepatic membranes [44], together with the presence of CBG inside the cells (which is likely to interfere competitively with the glucocorticoid's access to the nucleus), confers additional degrees of complexity on the mechanisms of action of CBG at the cellular level. More work is clearly needed to clarify these issues.…”
Section: Figure 7 Schematic Model Showing the Putative Influence Of Cmentioning
confidence: 99%
“…It is present not only in the plasma, but also inside cells as a result of either internalization or intracellular synthesis (reviewed in [12]). Moreover, the protein has the potential to interact with specific cell membrane receptors and eventually alter cAMP formation [13,14]. Because of the presence of PACAP receptors in the liver and evidence that Abbreviations used : CBG, corticosteroid-binding globulin ; CRE, cAMP response element ; dbcAMP, N 6 ,2h-O-dibutyryladenosine 3h,5h-phosphate ; PACAP, pituitary adenylate cyclase-activating polypeptide ; PLC, phospholipase C ; T 3 , tri-iodothyronine ; VIP, vasoactive intestinal polypeptide.…”
Section: Introductionmentioning
confidence: 99%